Concept of Penentuan Sebelum Pembagian (PSP) in the Distribution of Inheritance from Islamic Inheritance Perspective: Konsep Penentuan Sebelum Distribusi (PSP) dalam Distribusi Warisan dari Perspektif Warisan Islam - Kanggas, Fazari Zul Hasmi; Akmal, Haerul; Muthoharoh, Intan; Marjany, Nawa (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC UNIVERSITY, 2026)
The distribution of inheritance or inherited property is an issue that is always interesting to discuss in the academic world. Of course, there are many factors behind this, including the distribution of inheritance that is not in line with fiqh mawaris, or the use of terms that are often used as jargon in the distribution of inheritance, such as